Power system planning with emission constraints: Effects of CCS retrofitting - Krishna Priya, G. S. (Animo Repository, 2014)
Today, the world's energy needs are still supplied mainly from fossil fuel based resources. This is true for electricity generation as well, thus making the power sector responsible for 45% of greenhouse gas emissions. The present climate crisis has made it necessary to minimise emissions in power generation, with low-carbon energy sources taking on greater significance in recent years. However, most low-carbon sources have inherent problems, like intermittency and high capital expenditure. A suitable alternative is carbon capture and storage (CCS) technology which allows continued fossil fuel-based electricity generation at much lower rates of emission. Two approaches are possible in the deployment of CCS technology. The first is to introduce new power plants equipped for carbon dioxide (CO2) capture, while systematically shutting down existing coal power plants. Another is to retrofit existing power plants for CO2 capture. These approaches are compared in this work. The study shows that allowing CCS retrofitting of existing power plants can reduce the overall cost requirement significantly. In addition, a sensitivity analysis is also done to study the effect of nuclear energy on the overall energy mix. © 2013 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.